2016
DOI: 10.1136/heartjnl-2016-309458
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of β-blockers in heart failure and chronic obstructive pulmonary disease

Abstract: ObjectiveAlthough β-blockers are an established therapy in heart failure (HF) guidelines, including for patients with chronic obstructive pulmonary disease (COPD), there remain concerns regarding bronchoconstriction even with cardioselective β-blockers. We wished to assess the real-life use of β-blockers for patients with HF and comorbid COPD.MethodsWe evaluated data from the Optimum Patient Care Research Database over a period of 1 year for co-prescribing of β-blockers with either an ACE inhibitor (ACEI) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 31 publications
(25 reference statements)
2
48
1
4
Order By: Relevance
“…However, previous studies have highlighted that suboptimal HF pharmacotherapy is prevalent and there is often a risk-treatment mismatch where elderly patients at greatest risk of death after hospitalized HF are also less likely to receive a RASI or β-blocker. 23,24 Almost one-third of our cohort had a history of COPD which is the most powerful predictor of underuse of β-blockers in HF, 25 even though cardioselective β-blockers can be safely used in the majority of HF patients with COPD with the same mortality benefits. 26…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have highlighted that suboptimal HF pharmacotherapy is prevalent and there is often a risk-treatment mismatch where elderly patients at greatest risk of death after hospitalized HF are also less likely to receive a RASI or β-blocker. 23,24 Almost one-third of our cohort had a history of COPD which is the most powerful predictor of underuse of β-blockers in HF, 25 even though cardioselective β-blockers can be safely used in the majority of HF patients with COPD with the same mortality benefits. 26…”
Section: Discussionmentioning
confidence: 99%
“…only half of the COPD patients remain on chronic BB therapy after an episode of acute coronary syndrome. [9][10][11][12] In our patients the underutilization of BBs in heart failure was striking. However, in the setting of ischemic heart disease, the BB usage was proper.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Despite this, recent studies have demonstrated continuing under-prescription in suitable COPD patients with clear indications for beta-blocker therapy. 21,22 The safety of introducing beta-blockers during periods of acute respiratory illness, such as an acute exacerbation of COPD, remains unresolved. 8,23 To examine this, we performed a retrospective cohort study to assess the safety of beta-blocker initiation in patients admitted to hospital with an acute exacerbation of COPD.…”
Section: Introductionmentioning
confidence: 99%